Passive range of motion exercise to enhance growth in infants following the Norwood procedure: a safety and feasibility trial. (23rd March 2017) - Lambert, Linda M.; Trachtenberg, Felicia L.; Pemberton, Victoria L.; Wood, Janine; Andreas, Shelley; Schlosser, Robin; Barnard, Teresa; Daniels, Kaitlyn; Harrington, Ann T.; Dagincourt, Nicholas; Miller, Thomas A.
Abstract: Objective: The aim of this study was to evaluate the safety and feasibility of a passive range of motion exercise programme for infants with CHD. Study design: This non-randomised pilot study enrolled 20 neonates following Stage I palliation for single-ventricle physiology. Trained physical therapists administered standardised 15–20-minute passive range of motion protocol, for up to 21 days or until hospital discharge. Safety assessments included vital signs measured before, during, and after the exercise as well as adverse events recorded through the pre-Stage II follow-up. Feasibility was determined by the percent of days that >75% of the passive range of motion protocol was completed. Results: A total of 20 infants were enrolled (70% males) for the present study. The median age at enrolment was 8 days (with a range from 5 to 23), with a median start of intervention at postoperative day 4 (with a range from 2 to 12). The median hospital length of stay following surgery was 15 days (with a range from 9 to 131), with an average of 13.4 (with a range from 3 to 21) in-hospital days per patient. Completion of >75% of the protocol was achieved on 88% of eligible days. Of 11 adverse events reported in six patients, 10 were expected with one determined to be possibly related to the study intervention. There were no clinically significant changes in vital signs. At pre-Stage II follow-up, weight-for-age z-score (−0.84±1.20) and length-for-age z-score (−0.83±1.31) were higher compared with historical controls from two earlier trials. Conclusion: A passive range of motion exercise programme is safe and feasible in infants with single-ventricle physiology. Larger studies are needed to determine the optimal duration of passive range of motion and its effect on somatic growth.